THE USE OF CODE MIXING IN ELT: A CASE STUDY - Habso, Putri Ayu; Tahrun; Mulyadi (Universitas PGRI Palembang, 2025)
This study explores the phenomenon of code mixing in English Language Teaching (ELT) at SMP IT Al Hasanah Prabumulih, focusing on the types, frequency, and pedagogical relevance of its use in the classroom. Conducted between December 2023 and June 2024, this qualitative descriptive research utilized classroom observations and interviews to collect data. The findings indicate that both teachers and students employed three main types of code mixing: intra-sentential, intra-lexical, and phonological variation. Among these, intra-sentential code mixing emerged as the most dominant. Teachers perceived code mixing as an effective instructional strategy that supports vocabulary acquisition and facilitates learner comprehension, especially in a multilingual setting. Theoretically, this study enhances the understanding of code mixing as a communicative and instructional resource within ELT contexts. Practically, the findings offer valuable implications for educators, suggesting that code mixing, when used strategically, can bridge linguistic gaps and increase classroom engagement. Future research is recommended to further examine the long-term effects of code mixing on language proficiency and to explore its application in other educational settings. Additionally, comparative studies across different school levels and regions may yield broader insights into the pedagogical potential of code mixing.